1990
DOI: 10.1007/bf00176653
|View full text |Cite
|
Sign up to set email alerts
|

Improved production of heterologous protein from Streptomyces lividans

Abstract: Protein-secreting procaryotic host organisms are currently being sought as alternatives to Escherichia coli for recombinant processing. In this study we examined how manipulation of the cultivation conditions can enhance heterologous protein production by Streptomyces lividans. The recombinant S. lividans used in this study expressed and excreted a Flavobacterium enzyme capable of hydrolyzing organophosphates. Initial shake-flask studies demonstrated that supplementing Luria-Bertani medium with moderate amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…6). The effects of peptone on protein production in Streptomyces species were reported in other studies (Delacruz et al, 1992;Payne et al, 1990). Payne et al showed that degradation of heterologous protein could be prevented by the addition of peptone, resulting in an increase in enzyme productivity.…”
Section: Fed-batch Cultivationmentioning
confidence: 88%
“…6). The effects of peptone on protein production in Streptomyces species were reported in other studies (Delacruz et al, 1992;Payne et al, 1990). Payne et al showed that degradation of heterologous protein could be prevented by the addition of peptone, resulting in an increase in enzyme productivity.…”
Section: Fed-batch Cultivationmentioning
confidence: 88%
“…Limitations in DO after the cell growth became maximal or inadequate aeration may result in the low activity of the recombinant MtgA in the 250 l stirredtank fermenter. Feed-batch fermentation with continuous feeding of both glucose and tryptone may lead to a further increase in production of the enzyme [44], and we are continuing to investigate this possibility.…”
Section: Effects Of Metal Cations and Inhibitorsmentioning
confidence: 96%
“…With respect to filamentous fungi, expression systems using Streptomyces species as the host are particularly attractive, since they have been found capable of secreting high concentrations of enzymes [29]. Several researchers have investigated protein production from Streptomyces [30].…”
Section: Expression Systemsmentioning
confidence: 99%